¿Cuál es la labor profesional del maestro? - Gómez, Lorena (Góndola, enseñanza y aprendizaje de las ciencias, 2009)
This is a reflection on the question for the reasons of the teacher's lack of professional identity. We analyze whether the teacher sees himself as a mentor, a facilitator, a knowledge mediator, a class manager or a researcher. We believe that the work that teachers have developed mostly causes confusion when it comes to defining who they are and what their role is in education, moreover, probably if they ask themselves who they are, they have not an answer. This lack of professional identity on the part of the teacher is a problem that is currently experienced in classrooms and worse still, in universities where future teachers are educated. For this reason, it is necessary to ask, What causes such a professional defocus? What should be the role of the teacher? What should be his attitude towards education, facing problems, facing knowledge and facing the class? and if all these disadvantages arise, how should a teacher be educated to be able to feel and define himself professionally? These questions will be developed in the content of this writing, with two purposes, firstly I must identify myself as a teacher, being able to define who I am, my work and what are my professional goals, and secondly, so that people who read this essay reflects on their professional identity and their role as a producer of useful knowledge for society.